Evaluación in vitro de la fotoprotección del extracto de las hojas de Passiflora edulis “maracuyá” - Ruiz Gutierrez, Yusara Lisset (2018)
The main objective of this research was to evaluate the in vitro photoprotective effect of the extract of leaves of Passiflora edulis "maracuyá". To analyze the photoprotective capacity, the leaves of Passiflora edulis, from the Chumpón, Paiján, La Libertad sector, were collected. The hydroalcoholic extract of the leaves was obtained by the percolation method using as solvent ethanol of 70 ° GL until exhaustion. The concentration of the extract was determined by the weight of the dry extract, finding a value of 50 mg / mL. According to the methodology of Solar Protection Factor (SPF) in vitro described by Sayre and Mansur who based on the erythemogenic effect (ee) and the intensity of the radiation (I) to calculate the sun protection factor, the extract was analyzed in a spectrophotometer measuring the absorbances in the region of ultraviolet radiation B (290-320nm), the which can penetrate the epidermis by solar radiation and generate irreversible damage to the skin. It is concluded that the hydroalcoholic extract of leaves of Passiflora edulis "maracuya" had a medium photoprotective effect with an SPF of 14,598 according to COLIPA